Human Resources System For Small And Medium Sized Enterprises (SME-HR) - Muhammad Taufiq, Mohd Jaslan (2023)
Many companies in Malaysia have their own human resources department and use various methods to manage their work. One popular method is third-party Human Resources Management systems, which can help companies organize and ease their work. These systems can be found online, but they require a monthly payment. Even though most companies already use these systems, there are several companies, particularly Small and Medium-Sized Enterprises (SMEs), still do not. SMEs are businesses with a sales turnover of less than RM20 million or less than 75 full-time workers, including manufacturing, agriculture, construction, mining & quarrying, and services. There are a few SMEs that still use traditional, manual methods such as paper documents to save all the company's information, including employee details, medical leave letters, and reference receipts for claims. Traditional methods have several disadvantages, such as the potential loss of documents and difficulty searching for specific records. This can cause severe problems for SMEs if they continue to use these methods. There are several reasons why the SMEs still do not use a third-party system to manage their work, one of the reasons is the system's pricing. To overcome this problem, a proposed system, the Human Resources System for Small and Medium-Sized Enterprises (SME-HR), will be the perfect solution for SME companies to solve their problems. The purpose of this SME-HR system is to help the SME’s company to help them to ease their Human Resources workload. Besides that, to ensure this project will be successfully developed, Rapid Application Development or also known as RAD has been chosen. Due to that, it can help the SME company especially Anh Exora Enterprises which is the collaborator of this project to ease their Human Resources workload.